Background: Diseases experienced by the elderly are generally non-communicable diseases that are degenerative. Self-efficacy is an individual's belief in facing and solving problems he faces in various situations and being able to determine actions in completing certain tasks or problems, so that the individual is able to overcome obstacles and achieve the expected goals. Prolanis is a health service system and a proactive approach that is implemented in an integrated manner involving participan - Gaffar, Indra; Safira, Rifna; Ramadhany, Alifah Nur; Anggraeni, Najwaty; Yodang, Yodang; Harisa, Akbar; Syahrul, Syahrul; Zahra, Raudyatuh; Novitasari, Adani (Persatuan Perawat Nasional Indonesia (PPNI) Jawa Tengah., 2021)
Background: Diseases experienced by the elderly are generally non-communicable diseases that are degenerative. Self-efficacy is an individual's belief in facing and solving problems he faces in various situations and being able to determine actions in completing certain tasks or problems, so that the individual is able to overcome obstacles and achieve the expected goals. Prolanis is a health service system and a proactive approach that is implemented in an integrated manner involving participants, health facilities and BPJS health in the context of health care for BPJS Health participants who suffer from chronic diseases to achieve optimal quality of life with effective and efficient health care costs. Objectives: the purpose of this study was to determine the effect of sociodemographic characteristics on Self-Efficacy among Elderly with Chronic Diseases who attend the Prolanis Program in Makassar City. Design: this research is a quantitative study with a descriptive cross-sectional study approach. Population and sample are elderly with chronic disease who follow the prolanis program in the work area of ​​Bira Health Center and Minasa Upa Health Center Makassar City. Results: the study results identified the marriage status affect the Self Efficacy in the elderly who suffer from chronic diseases in Makassar City. In addition, the prolanis program also could help the elderly to increase their self-efficacy in dealing with the disease they were experiencing.